STRUKTUR DAN KOMPOSISI VEGETASI DAERAH PASCA BANJIR DI NEGERI KAMARIAN KECAMATAN KAIRATU KABUPATEN SERAM BAGIAN BARAT - Sapiya, Danielle Allesandro; Sahupala, Andjela; Tetelay, Febian (MARSEGU : Jurnal Sains dan Teknologi, 2025)
The objective of this study was to determine the structure and composition of natural forest vegetation following post-flood conditions in Kamarian Village, Kairatu District, West Seram Regency. Vegetation analysis was employed by collecting data on species types, number, diameter, and tree height. The data collection method in this study utilized the continuous strip sampling method and line plot sampling method with 100% intensity. The research area covered 3 hectares (30,000 m²) consisting of a transect length of 500 meters and an observation strip width of 20 meters. The results showed that the vegetation structure in the post-flood area consisted of four strata: Stratum A (tall trees), Stratum B (medium trees), Stratum C (lower trees), Stratum D (shrubs and ferns), and Stratum E (ground cover layer). The dominant species in each stratum varied; however, they were generally dominated by Pulai (Alstonia scholaris), Pulaka (Octomeles sumatrana), and Salam (Syzygium polyanthum). The vegetation composition in the post-flood area indicated moderate species diversity, with the dominance of several species showing adaptive value. The Importance Value Index (IVI) at each growth stage (trees, poles, saplings, and seedlings) demonstrated that Pulai, Pulaka, and Salam play a very important role in the plant community at the research location.